Discrepancy Principle for Solving Periodic Integral Equations of the First Kind - Semenova, E.V.; Volynets, E.A. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2017)
Fully discrete projection method with discrepancy principle is considered for solving periodic integral equations of the first kind with unknown smoothness of solution. For proposed approach it is proved the optimality and effectiveness in the sense of computational resource.